Grazlng Studies with Ramlambs of Marwarl Breed on Cenchrus-Aristida Rangelands - Rathore, S S (Annals of Arid Zone, 2016)
Comparative studies on continuous versus deferred rotational grazing system were carried out from August 1978 to July 1983 with ramlambs of Marwari breed on Cellchrus-Aristida grass cover at Bhopalgarh. The Average body weight gain was higher in continuous grazing system then deferred rotational grazing system. The forage production did not vary much in both the system of grazing. However, year to year variation in body weight gain and forage yield was due to variation in rainfall.